Visible-light photoredox catalyzed synthesis of pyrroloisoquinolines via organocatalytic oxidation/[3 + 2] cycloaddition/oxidative aromatization reaction cascade with Rose Bengal - Vila, Carlos; Lau, Jonathan; Rueping, Magnus (Beilstein Journal of Organic Chemistry, 2014)
Pyrrolo[2,1-a]isoquinoline alkaloids have been prepared via a visible light photoredox catalyzed oxidation/[3 + 2] cycloaddition/oxidative aromatization cascade using Rose Bengal as an organo-photocatalyst. A variety of pyrroloisoquinolines have been obtained in good yields under mild and metal-free reaction conditions.
Keywords: alkaloids; [3 + 2] cycloaddition; organocatalysis; oxidation; photochemistry; photoredox catalysis; Rose Bengal; visible-light

(untitled) - Bailly, C. (Curr. Med. Chem.: Anti-Cancer Agents, 2004)

(untitled) - Handy, S. T.; Zhang, Y. (Org. Prep. Proced. Int., 2005)

(untitled) - Fan, H.; Peng, J.; Hamann, M. T.; Hu, J.-F. (Chem. Rev., 2008)

(untitled) - Pla, D.; Albericio, F.; Alvarez, M. (Anti-Cancer Agents Med. Chem., 2008)

(untitled) - Marco, E.; Laine, W.; Tardy, C.; Lansiaux, A.; Iwao, M.; Ishibashi, F.; Bailly, C.; Gago, F. (J. Med. Chem., 2005)

(untitled) - Reddy, M. V. R.; Rao, M. R.; Rhodes, D.; Hansen, M. S. T.; Rubins, K.; Bushman, F. D.; Venkateswarlu, Y.; Faulkner, D. (J. Med. Chem., 1999)

(untitled) - Aubry, A.; Pan, X.-S.; Fisher, L. M.; Jarlier, V.; Cambau, E. (Antimicrob. Agents Chemother., 2004)

(untitled) - Reddy, S. M.; Srinivasulu, M.; Satanarayana, N.; Kondapi, A. K.; Venkateswarlu, Y. (Tetrahedron, 2005)

(untitled) - Quesada, A. R.; Garcia Grávalos, M. D.; Fernández Puentes, J. L. (Br. J. Cancer, 1996)

(untitled) - Heim, A.; Terpin, A.; Steglich, W. (Angew. Chem., Int. Ed. Engl., 1997)

(untitled) - Ploypradith, P.; Mahidol, C.; Sahakitpichan, P.; Wongbundit, S.; Ruchirawat, S. (Angew. Chem., Int. Ed., 2004)

(untitled) - Boger, D. L.; Boyce, C. W.; Labroli, M. A.; Sehon, C. A.; Jin, Q. (J. Am. Chem. Soc., 1999)

(untitled) - Banwell, M. G.; Flynn, B. L.; Stewart, S. G. (J. Org. Chem., 1998)

(untitled) - Handy, S. T.; Zhang, Y.; Bregman, H. (J. Org. Chem., 2004)

(untitled) - Ploypradith, P.; Kagan, R. K.; Ruchirawat, S. (J. Org. Chem., 2005)

(untitled) - Ohta, T.; Fukuda, T.; Ishibashi, F.; Iwao, M. (J. Org. Chem., 2009)

(untitled) - Gupton, J. T.; Clough, S. C.; Miller, R. B.; Lukens, J. R.; Henry, C. A.; Kanters, R. P. F.; Sikorski, J. A. (Tetrahedron, 2003)

(untitled) - Fujikawa, N.; Ohta, T.; Yamaguchi, T.; Fukuda, T.; Ishibashi, F.; Iwao, M. (Tetrahedron, 2006)

(untitled) - Chen, L.; Xu, M.-H. (Adv. Synth. Catal., 2009)

(untitled) - Yadav, J. S.; Gayathri, K. U.; Reddy, B. V. S.; Prasad, A. R. (Synlett, 2009)

(untitled) - Najera, C.; Sansano, J. M. (Curr. Org. Chem., 1998)

(untitled) - Ishibashi, F.; Miyazaki, Y.; Iwao, M. (Tetrahedron, 1997)

(untitled) - Banwell, M. G.; Flynn, B. L.; Hockless, D. C. R. (Chem. Commun., 1997)

(untitled) - Cironi, P.; Manzanares, I.; Albericio, F.; Álvarez, M. (Org. Lett., 2003)

(untitled) - Ploypradith, P.; Petchmanee, T.; Sahakitpichan, P.; Litvinas, N. D.; Ruchirawat, S. (J. Org. Chem., 2006)

(untitled) - Grigg, R.; Heaney, F. (J. Chem. Soc., Perkin Trans. 1, 1989)

(untitled) - Su, S.; Porco, J. A., Jr (J. Am. Chem. Soc., 2007)

(untitled) - Yu, C.; Zhang, Y.; Zhang, S.; Li, H.; Wang, W. (Chem. Commun., 2011)

(untitled) - Zou, Y.-Q.; Lu, L.-Q.; Fu, L.; Chang, N.-J.; Rong, J.; Chen, J.-R.; Xiao, W.-J. (Angew. Chem., Int. Ed., 2011)

(untitled) - Huang, L.; Zhao, J. (Chem. Commun., 2013)

(untitled) - Guo, S.; Zhang, H.; Huang, L.; Guo, Z.; Xiong, G.; Zhao, J. (Chem. Commun., 2013)

(untitled) - Wang, H.-T.; Lu, C.-D. (Tetrahedron Lett., 2013)

(untitled) - Zeitler, K. (Angew. Chem., Int. Ed., 2009)

(untitled) - Yoon, T. P.; Ischay, M. A.; Du, J. (Nat. Chem., 2010)

(untitled) - Narayanam, J. M. R.; Stephenson, C. R. J. (Chem. Soc. Rev., 2011)

(untitled) - Xuan, J.; Xiao, W.-J. (Angew. Chem., Int. Ed., 2012)

(untitled) - Shi, L.; Xia, W. (Chem. Soc. Rev., 2012)

(untitled) - Prier, C. K.; Rankic, D. A.; MacMillan, D. W. C. (Chem. Rev., 2013)

(untitled) - Hu, J.; Wang, J.; Nguyen, T. H.; Zheng, N. (Beilstein J. Org. Chem., 2013)

(untitled) - Ravelli, D.; Fagnoni, M. (ChemCatChem, 2012)

(untitled) - Ravelli, D.; Fagnoni, M.; Albini, A. (Chem. Soc. Rev., 2013)

(untitled) - Nicewicz, D. C.; Nguyen, T. M. (ACS Catal., 2014)

(untitled) - Liu, H.; Feng, W.; Kee, C. W.; Zhao, Y.; Leow, D.; Pan, Y.; Tan, C.-H. (Green Chem., 2010)

(untitled) - Pan, Y.; Kee, C. W.; Chen, L.; Tan, C.-H. (Green Chem., 2011)

(untitled) - Pan, Y.; Wang, S.; Kee, C. W.; Dubuisson, E.; Yang, Y.; Loh, K. P.; Tan, C.-H. (Green Chem., 2011)

(untitled) - Neumann, M.; Füldner, S.; König, B.; Zeitler, K. (Angew. Chem., Int. Ed., 2011)

(untitled) - Hari, D. P.; König, B. (Org. Lett., 2011)

(untitled) - Liu, Q.; Li, Y.-N.; Zhang, H.-H.; Chen, B.; Tung, C.-H.; Wu, L.-Z. (Chem.–Eur. J., 2012)

(untitled) - Fidaly, K.; Ceballos, C.; Falguières, A.; Veitia, M. S.-I.; Guy, A.; Ferroud, C. (Green Chem., 2012)

(untitled) - Fu, W.; Guo, W.; Zou, G.; Xu, C. (J. Fluorine Chem., 2012)

(untitled) - Hari, D. P.; Schroll, P.; König, B. (J. Am. Chem. Soc., 2012)

(untitled) - Hari, D. P.; Hering, T.; König, B. (Org. Lett., 2012)

(untitled) - Neumann, M.; Zeitler, K. (Org. Lett., 2012)

(untitled) - Hamilton, D. S.; Nicewicz, D. A. (J. Am. Chem. Soc., 2012)

(untitled) - Rueping, M.; Vila, C.; Bootwicha, T. (ACS Catal., 2013)

(untitled) - Grandjean, J.; Nicewicz, D. A. (Angew. Chem., Int. Ed., 2013)

(untitled) - Riener, M.; Nicewicz, D. A. (Chem. Sci., 2013)

(untitled) - Wilger, D. J.; Gesmundo, N. J.; Nicewicz, D. A. (Chem. Sci., 2013)

(untitled) - Nguyen, T. M.; Nicewicz, D. A. (J. Am. Chem. Soc., 2013)

(untitled) - Perkowski, A. J.; Nicewicz, D. A. (J. Am. Chem. Soc., 2013)

(untitled) - Pitre, S. P.; McTiernan, C. D.; Ismaili, H.; Scaiano, J. C. (J. Am. Chem. Soc., 2013)

(untitled) - Rueping, M.; Vila, C.; Koenings, R. M.; Poscharny, K.; Fabry, D. C. (Chem. Commun., 2011)

(untitled) - Rueping, M.; Zhu, S.; Koenings, R. M. (Chem. Commun., 2011)

(untitled) - Rueping, M.; Leonori, D.; Poisson, T. (Chem. Commun., 2011)

(untitled) - Rueping, M.; Zhu, S.; Koenings, R. M. (Chem. Commun., 2011)

(untitled) - Rueping, M.; Zoller, J.; Fabry, D. C.; Poscharny, K.; Koenings, R. M.; Weirich, T. E.; Mayer, J. (Chem.–Eur. J., 2012)

(untitled) - Rueping, M.; Koenings, R. M.; Poscharny, K.; Fabry, D. C.; Leonori, D.; Vila, C. (Chem.–Eur. J., 2012)

(untitled) - Rueping, M.; Vila, C.; Szadkowska, A.; Koenigs, R. M.; Fronert, J. (ACS Catal., 2012)

(untitled) - Zhu, S.; Rueping, M. (Chem. Commun., 2012)

(untitled) - Zhu, S.; Das, A.; Bui, L.; Zhou, H.; Curran, D. P.; Rueping, M. (J. Am. Chem. Soc., 2013)

(untitled) - Rueping, M.; Vila, C. (Org. Lett., 2013)

(untitled) - Vila, C.; Rueping, M. (Green Chem., 2013)

(untitled) - Tóth, J.; Váradi, L.; Dancsó, A.; Blaskó, G.; Töke, L.; Nyerges, M. (Synlett, 2007)